Isolation and Identification of Three Alkaloids Compounds from Albizia lebbeck L.Leaves and study of Their Antimicrobial Activity Against Pathogenic Bacteria of Urinary Tracts Inflammatory in vitro - Shenta, Ashwaq Abood (University of Thi-Qar Journal of Science, 2013)
Three alkaloidic compounds are 3,3-dimethyl-4-(1-aminoethyl)- Azetidin-2-one, 2,4-Bis( hydroxylamino)- 5-nitropyrimidine and 2-Amino-4-hydroxy pteridine-6-carboxylic acid were isolated and purified from Albizia lebbeck L.leaves. Gas chromatography- mass spectrum technique, thin layer chromatography and column chromatography were carried out for identification of chemical structures of these compounds. Antimicrobial activity of the three alkaloids were recorded against pathogenic bacteria of urinary tracts represented byProteus sp., Klebsiella sp., Pseudomonas aeruginosa, Escherichia coli and Staphylococcus aureus. The highest inhibition zone diameter was measured for the mixture of alkaloidic compounds against Staphylococcus aureus bacteria with value equal to 42 mm at concentration 150 mg/ml whereas the highest inhibition zone diameter was recorded for 2-Amino-4-hydroxypteridine-6-carboxylic acid compound against Staphylococcus aureus bacteria with value equal to 23 mm at the same concentration. Cytotoxicity detectionproved that all alkaloid compounds have no toxicity towards red blood cells. Therefore the three alkaloids can be used as medicinal herbal substituents to treat urinary tract Inflammatory instead of antibiotics but this work demands further pharmaceutical and clinical studies.